Safety and efficacy of biodegradable polymer biolimus-eluting stents in patients with non-ST-elevation acute coronary syndrome: a pooled analysis of GLASSY and TWILIGHT. (3rd October 2022) - Mehran, R; Spirito, A; Cao, D; Sartori, S; Baber, U; Dangas, G; Gibson, C M; Steg, P G; Pocock, S J; Valgimigli, M
Abstract: Background: Biodegradable polymer (BP) drug-eluting stents (DES) have shown similar safety and efficacy compared with second-generation durable polymer (DP)-DES in several randomized trials and meta-analyses. However, study participants were generally maintained on a standard dual antiplatelet therapy (DAPT) for at least 6 months after percutaneous coronary intervention (PCI). Therefore, the differences in thrombogenicity between these two stent technologies may have been unappreciated, especially among patients with acute coronary syndrome (ACS). Purpose: We aimed to compare the safety and efficacy of BP Biolimus-Eluting Stent (BP-BES) versus 2nd generation DP-DES among ACS patients undergoing PCI and receiving ticagrelor alone or in combination with aspirin. Methods: We pooled individual patient-level data from two randomized controlled trials, the Ticagrelor With Aspirin or Alone in High-Risk Patients After Coronary Intervention (TWILIGHT, n=9, 006) (1) and the GLOBAL LEADERS Adjudication Sub-Study (GLASSY, n=7, 585) (2). In order to reduce biases related to trial design differences, only NST-ACS patients not fulfilling any exclusion criterion of both studies were included and 2 separate analysis for short (0 to 3 months after PCI) and long-term (3 to 12 months after PCI) outcomes were performed. Patients were stratified according to the stent used at index PCI (BP-BES vs 2nd generation DP-DES). In both analysis, the primary outcome was major adverse cardiovascular events (MACE, a composite of cardiovascular death, myocardial infarction and definite or probable stent thrombosis); the key secondary outcomes were target-vessel failure (TVF) and BARC 2, 3 or 5 bleeding. Events rate and risk were assessed separately for the two study periods and subsequently 12-months risk estimates were derived by pooling the results of the two analysis. Results: Out of 7, 729 and 6, 572 NST-ACS patients included in the two analysis, 2, 321 (30%) and 2, 211 (33.6%) received a BP-BES, respectively. Among patients treated with BP-BES versus DP-DES, the occurrence of MACE was similar at 3 months after PCI (1.1% vs 1.4%, adjusted HR 0.81, 95% CI 0.51–1.29), while it was significantly lower in the former group between 3 and 12 months (1.7% vs 3.1%, adj. HR 0.46, 95% CI 0.32–0.67) and in the overall period (pooled adjusted HR estimate 0.58, 95% CI 0.43–0.77). Similarly, significant differences were observed for TVF and BARC 2, 3, or 5 bleeding, whose risk at 12 months was lower among BP-BES than DP-DES patients (pooled adj. HR estimate 0.49, 95% CI 0.38–0.63 and 0.79, 95% CI 0.79, 95% CI 0.65–0.97, respectively). Conclusion: As compared to 2nd generation DP-DES, BP-BES was associated with a lower risk of MACE, TVF and bleeding among NST-ACS patients undergoing PCI and treated with ticagrelor with or without aspirin. The findings of this analysis are exploratory and need further confirmation. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Biosensors (Singapore)